Effect of Lactobacillus fermentum ZS40 on the NF-κB signaling pathway in an azomethane-dextran sulfate sodium-induced colon cancer mouse model - Liu, Jia; Wang, Shuaiqi; Yi, Ruokun; Long, Xingyao; Zhao, Xin (Frontiers in Microbiology, 2022)
In our study, we explored the effect of Lactobacillus fermentum ZS40 on the NF-κB signaling pathway in a mouse model of colon cancer induced by azoxymethane-dextran sodium sulfate (AOM-DSS). In the experiment, sixty mice were grouped into six groups, ten animals for each. (NC) normal animals received normal saline. In the other five groups, mice were used as a colon cancer model induced with AOM-DSS. (CRC) group received normal saline; (ZS40-H) group was treated with high-dose Lactobacillus fermentum ZS40; (ZS40-L) group treated with low-dose Lactobacillus fermentum ZS40; (BLA) group treated with Lactobacillus bulgaricus (Bulgarian strain; BLA); and finally (SD) group treated with sulfasalazine. Body weights and bowel movements were observed during the feeding period. Serum levels of indicators IL-1β, IL-8, TNF-α, MIP-1β, and VCAM-1 were measured. The expression levels of inflammation-related genes were assessed using qPCR. In the groups treated with Lactobacillus fermentum ZS40, the expression of inflammatory stimulating factors TNF-α and IL-1β protein was decreased; the expression of key proteins IκBα and p65 in the pathway was also decreased, resulting in decreased expression of the target protein Cox- 2. ZS40-H and SD had the best intervention effect than ZS40-H and BLA (p < 0.05). This study concludes that edible Lactobacillus fermentum ZS40 could regulate the expression of inflammation-related genes in model mice and alleviate inflammation.